Spatio-Temporal Characteristics and Trend Analysis of Grassland Ecosystem Drought in Asia From 2010 to 2018 - Zhang, Xun; Liang, Yike; Li, Xiang; Lin, Gang; Liu, Ying (Frontiers in Ecology and Evolution, 2021)
Under the background of global climate change, the impact from drought on ecosystem exhibits the characteristics of complexity and multi-process, especially for the main component: grassland ecosystem of the overall ecosystem. It is very important for drought response and prevention to determine the past drought and evaluate the development trend of drought. In this research, land surface temperature data and vegetation index data obtained by Google Earth Engine (GEE) were used to construct Land Surface Temperature-Enhanced Vegetation Index (LST-EVI) feature spaces, by solving the dry and wet edge fitting equations to calculate the Temperature Vegetation Drought Index (TVDI), and then the degree of drought and its spatial distribution and change conditions of Asian Grassland Ecosystem (AGE) were obtained. The drought trend of AGE was analyzed by using Sen trend test. The results showed that there were obvious spatial differences in the wet and dry conditions of AGE. There was an increase in soil drought from east to west and from north to south, with humid areas mainly concentrated in northern Asia and severe drought areas concentrated in southern Asia. From 2010 to 2018, the area of humid areas and severe drought areas of AGE decreased, and some humid areas changed to normal areas or even drought areas. Drought is worsening, while the drought in severe drought areas was alleviated. There is an obvious increased trend towards drought degrees in AGE, such as Russia, Kazakhstan, China, Mongolia and other countries or regions. In addition to severe drought areas, those areas should also be the focus areas for drought prevention in future.